Peculiarities and prospects of development of contemporary retailing: the global and Ukrainian realities - Chorna, Maryna; Shumilo, Olga; Kushnir, Tamila; Zabrodska, Hanna (International Journal of Economics and Financial Issues, 2018)
Researching the current state and possible prospects of development of the trade industry is of considerable importance under contemporary conditions. The article considers the role of retail trade in the national economy of the country. The authors have determined the meaning of retailing and inherent peculiarities of retailers stipulated by the national specificity. Having examined dynamics of development of retailing, the authors reveal a positive tendency and peculiarities of the dynamics. Over the last few years, retail sales of enterprises operating in the retail sector and the amount of retail space have increased. Furthermore, large retailers acquire small stores. The authors have examined the current state and peculiarities of development of retail chains in Ukraine compared with chains of other countries and indicated problems of their development. The authors have analyzed retail sales for the whole country and in the regions of Ukraine as the main indices characterizing development of retailing. The article analyzes the contemporary global tendencies of development of retailing and its specificity in the context of the following tendencies: partnership; acquisition; the merger of offline and online trading; development of innovations and new technologies in retailing; formation of loyalty of customers in Ukraine, as well as all around the world. Keywords: retailing, trade networks, Ukraine, peculiarities of trade, innovations in retailing, tendencies of development. JEL Classifications: L81, M30, L10, O30